2021
DOI: 10.3389/feart.2021.679689
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Climate Variability During the Last 5000 Years From the Banni Plains, Kachchh, Western India

Abstract: The climatic conditions during the beginning of the last 5,000 years have been discussed, debated, and documented from various parts of the Indian subcontinent, due to the human–climate interrelationship. In the present study, we report a multi-proxy dataset encompassing the widely used ∼ geochemical and mineral magnetic proxies supported by radiocarbon and optical chronologies from the Banni Plains of the Rann of Kachchh, western India. Our results support the earlier observations of the prolonged wetter clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Dixit et al (2018) also reported intensified dry conditions from 4.4 to 3.2 cal kyrs BP as indicated by the complete drying of the Karsandi playa lake, followed by aeolian deposition at its location. Makwana et al (2021) suggested arid phase occurring during 4.8–4.4 cal kyrs BP, 3.3–3 cal kyrs BP and at 2.4 cal kyrs BP from the geochemical and mineral magnetic proxies-based analysis of sediments from Banni grassland, Rann of Kachchh. Whereas phases of humid climatic conditions have been reported by this study during >4.8 cal kyrs BP, 4–3 cal kyrs BP, 1.9–1.4 cal kyrs BP and 0.9–0.5 cal kyrs BP.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dixit et al (2018) also reported intensified dry conditions from 4.4 to 3.2 cal kyrs BP as indicated by the complete drying of the Karsandi playa lake, followed by aeolian deposition at its location. Makwana et al (2021) suggested arid phase occurring during 4.8–4.4 cal kyrs BP, 3.3–3 cal kyrs BP and at 2.4 cal kyrs BP from the geochemical and mineral magnetic proxies-based analysis of sediments from Banni grassland, Rann of Kachchh. Whereas phases of humid climatic conditions have been reported by this study during >4.8 cal kyrs BP, 4–3 cal kyrs BP, 1.9–1.4 cal kyrs BP and 0.9–0.5 cal kyrs BP.…”
Section: Introductionmentioning
confidence: 97%
“…Karsandi (Dixit et al, 2018); 26. Banni Grassland (Makwana et al, 2021); 27. Luni, Sabarmati and Mahi River (Jain et al, 2004); 28.…”
Section: Introductionmentioning
confidence: 99%